Incidence of Vitamin D Levels in Cord Blood of Newborns and Correlation with Maternal Vitamin D: Our Experience (Indian Journal of Public Health Research & Development, 2021)
Vitamin D deficiency is common in northern India but there are limited data in pregnant women andneonates. This study aimed to determine the prevalence of vitamin D levels in cord blood of newborns andthe association with maternal vitamin D. A total of 50 pregnant women and their neonates were included.Clinical data and venous maternal blood for calcium,phosphate, albumin, alkaline phosphatase, magnesium,intact parathyroid hormone, and vitamin D were obtained on the day of labor. Cord blood was collectedfollowing delivery to evaluate vitamin D status of newborns. Mean serum maternal and cord blood 25OHDlevels were 25.42 ± 8.07 and 14.85 ± 5.13 ng/mL. The prevalence of vitamin D deficiency (25OHD < 12 ng/mL) and insufficiency (25OHD 12–20ng/mL) in cord blood of newborns were 20.2 and 69.1%,respectively.There was a significant correlation between maternal and cord blood vitamin D levels (P< 0.001). Thefactors associated with cord blood vitamin D deficiency were low maternal 25OHD level and no vitamin Dsupplement during pregnancy.Conclusion: There is a high prevalence of vitamin D deficiency among the neonates. Adequate prenatalvitamin D supplementation should be implemented as routine antenatal care.
Keywords: Vitamin D deficiency. Cordblood. Newborns. Pregnancy